Crystal structure of MgK0.5[B6O10](OH)0.5·0.5H2O, poly[dimagnesium potassium bis(hexaborate) hydroxide monohydrate] - Qi-Ming Qiu; Jian-Biao Song (Acta Crystallographica Section E: Crystallographic Communications, 2022)
The solvothermal reaction of H3BO3, KCF3SO3, Mg(CF3SO3)2 and pyridine led to a new alkali- and alkaline-earth-metal borate, MgK0.5[B6O10](OH)0.5·0.5H2O. Its structure features an intricate three-dimensional framework built from [B6O13]8− clusters, thus resulting in a six-connected achiral net with high symmetry. Each [B6O13]8− building block is composed of three trigonal BO3 and three tetrahedral BO4 units, with these BO4 units being further connected to neighboring BO3 units, giving rise to an oxoboron cluster of the general formula [B6O10]2−.